An Unusual Case of Severe Persistent Neonatal Thrombocytopenia in an Extremely Low Birth Weight, Extreme Preterm Neonate - Mobin Paul MBBS, MD, DM; Ananthen Killikulangara Sadanandan MBBS, MD, Fellow in Neonatology; Latha Abraham MBBS, MD; Sophy Madany Pathrose MBBS; Dasary Varghese MBBS (SAGE Publishing, 2021)
Neonatal thrombocytopenia is a common hematological problem but refractory thrombocytopenia is very rare in neonates. A systematic and diligent workup will result in arriving at the proper diagnosis and providing accurate management in rare causes of neonatal thrombocytopenia. We report a case of severe refractory thrombocytopenia in an extremely low birth weight (ELBW)/extreme preterm baby who presented with early onset severe thrombocytopenia associated with anemia and required multiple platelet transfusions. After ruling out COVID-19 infection, sepsis and neonatal alloimmune thrombocytopenia (NAIT), the cause for severe refractory thrombocytopenia was diagnosed as Type II congenital amegakaryocytic thrombocytopenia (CAMT) by bone marrow examination and MPL gene mutation studies.